Plastic bending of sheet metal with tension/compression asymmetry. (November 2020) - Ahn, Kanghwan
Abstract: The plastic bending of a sheet metal having tension/compression asymmetry was investigated in this work with AZ31B Mg sheets, particularly focused on its deformation behavior. With the assumptions of pure bending and rigid plasticity, analytic expressions were obtained to describe sheet bending under the plane strain condition, taking into account the movement of the neutral surface and the associated deformation histories of longitudinal fibers in the sheet. Mechanical properties associated with bending such as anisotropy, work hardening in tension and compression, and untwinning under compression-tension were characterized considering the intricate hardening nature of AZ31B Mg sheet at room temperature. With the material coefficients characterized, the analytical expressions of bending were solved incrementally by numerical procedures. The computed thicknesses were compared to the thicknesses of V-die bending tests for validation purposes. It was found that the bending formulation reflecting the tension/compression asymmetry of AZ31B Mg sheet predicts the thickness increase at the initial stage of bending numerically, in agreement with the experimental results. Besides, the thickness variation during bending was found to be significantly affected by the asymmetric R-values of AZ31B Mg sheet. These results were discussed in connection with the movement of the neutral surface, as well as the material asymmetry in tension and compression.